Penerapan Metode Association Rule Menggunakan Apriori untuk Rekomendasi Penyusunan Rak Buku di Perpustakaan Universitas Muhammadiyah Bengkulu - M Rafli Yudhatama; Ardi Wijaya; Dedy Abdullah; Anisya Sonita (Universitas Dehasen Bengkulu, 2024)
The library is one of the facilities provided by Muhammadiyah University. The Muhammadiyah University Library can provide various kinds of library materials such as textbooks, text books, literature for practicums, general magazines and various other collections. Some book collections can be borrowed or can only be accessed on site. Apriori is an algorithm that is well known for searching frequent item sets using association rule techniques. The a priori algorithm uses knowledge about previously known frequent itemsets to process further information. In the a priori algorithm, to determine the candidates that may appear, it is done by paying attention to the minimum support. The data collection techniques used by the author in this research are interview techniques, observation and literature study. To carry out a bookshelf search application in a library, it begins with the process of inputting the book title, author's name, and publisher through inputting search data. Next, the system will look for a match string which will be processed by the application. If each string is found it will display it as a whole and will provide bookshelf information. The conclusion that can be drawn from the application of the association rule method using a priori for recommendations for arranging bookshelves in the Muhammadiyah University of Bengkulu library, is that you can find the placement of books in the library by applying the association rule method, can distribute books grouped according to scientific discipline categories, and the rapid miner application By using the association rule method, you can also read scientific discipline categories from the same book and the title entered contains the same characters but different writing.